Beyond the State: Global Policy and Transnational Administration - Kim Moloney; Diane Stone (International Review of Public Policy)
The conceptual distance between the sovereign state and the global domain of policy making and administration is narrowing, challenging the prevailing methodological nationalism. The rise of global policy and transnational administration necessitates new conversations for traditional, often domestically focused, public policy and public administration studies. By expanding our analytical, theoretical, conceptual, and even our pedagogical approaches to include the kaleidoscope of global governance actors, levels of analysis, sectors, and concepts, not only is our policy research enhanced and deepened, but our ability to engage this complexity is enhanced.